APLIKASI PENGAJUAN PROPOSAL BANTUAN PADA DINAS PETERNAKAN KABUPATEN SIDENRENG RAPPANG - Darma, Humairoh Salsabila; Marlina, Marlina; Yunus, Mughaffir (LPPM Universitas Putera Batam, 2025)
The livestock sector is a leading sector after agriculture. This is evident in the numerous livestock businesses, both large and small, that are developing in the Sidenreng Rappang area. However, in supporting the development of this sector, the current process for submitting assistance proposals still faces various obstacles, such as a manual submission system, inefficient processes, and a lack of transparency in verification and selection. Due to these obstacles, farmers can now submit assistance proposals electronically through this application. The integrated system within this application will enable a more transparent proposal selection process and real-time access by relevant parties, including the livestock service. The development method used in creating this application is R&D, which includes needs analysis, system design, implementation, testing, and maintenance. One of the stages is an information system built using a web-based system and a database system as its storage medium. This system was built using PHP and MySQL, then integrated with PHPMyAdmin using XAMPP as the local host. Furthermore, this application also helps the Sidenreng Rappang Regency Office provide an effective and efficient solution for the proposal submission process.